(untitled) (Journal of the College of Basic Education, 2022)
Research time Methods of preparation and chemical properties of cyclic derivatives 1,3,4- oxadiazole substituted at the site 2,5. What are the procedures for preparing liquid crystalline polymers from 1,3,4- oxadaya heterocyclic compounds and spectroscopic methods